Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1101/gr.141945.112
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent stem cells escape from senescence-associated DNA methylation changes

Abstract: Pluripotent stem cells evade replicative senescence, whereas other primary cells lose their proliferation and differentiation potential after a limited number of cell divisions, and this is accompanied by specific senescence-associated DNA methylation (SA-DNAm) changes. Here, we investigate SA-DNAm changes in mesenchymal stromal cells (MSC) upon longterm culture, irradiation-induced senescence, immortalization, and reprogramming into induced pluripotent stem cells (iPSC) using high-density HumanMethylation450 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
154
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 115 publications
(163 citation statements)
references
References 78 publications
(87 reference statements)
5
154
2
1
Order By: Relevance
“…These regulatory proteins included transcriptional repressor CTCF, polycomb protein EZH2 and histone 2A member Z. A previous study by Koch et al, using pluripotent stem cells, linked regions of senescence-associated hypomethylation to binding sites for polycomb proteins (49). While we could not access data for all of the polycomb proteins they investigated, both our study and theirs observed focal hypomethylation at EZH2 binding sites.…”
Section: Results Summary and Comparison With Literaturecontrasting
confidence: 41%
“…These regulatory proteins included transcriptional repressor CTCF, polycomb protein EZH2 and histone 2A member Z. A previous study by Koch et al, using pluripotent stem cells, linked regions of senescence-associated hypomethylation to binding sites for polycomb proteins (49). While we could not access data for all of the polycomb proteins they investigated, both our study and theirs observed focal hypomethylation at EZH2 binding sites.…”
Section: Results Summary and Comparison With Literaturecontrasting
confidence: 41%
“…iPS cells show high Ezh2 expression (Fig. 1A-D) and also overcome senescence [36]. Therefore, iPS cell generation appears to be linked to high Ezh2 expression.…”
Section: Forced Ezh2 Expression Enhances Reprogramming Efficiencymentioning
confidence: 99%
“…Some of these senescence-associated DNAm (SA-DNAm) changes are almost linearly acquired during culture expansion and can therefore be used as biomarker for the state of cellular aging (57). Notably, SA-DNAm changes are enriched in developmental genes, such as homeobox genes, and they can be reversed by reprogramming into induced pluripotent stem cells (iPSCs) (4,7,8). This indicates that SA-DNAm changes—and hence also the process of replicative senescence—are somehow regulated, but the underlying mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%